Search for a Charged Higgs Boson Produced in the Vector-Boson Fusion Mode with Decay H(±)→W(±)Z using pp Collisions at √s=8 TeV with the ATLAS Experiment - Aad, G; Abbott, B; Abdallah, J; Abdinov, O; Aben, R; Abolins, M; AbouZeid, O S; Abramowicz, H; Abreu, H; Abreu, R; Abulaiti, Y; Acharya, B S; et al. (Physical review letters, 2015)
A search for a charged Higgs boson, H(±), decaying to a W(±) boson and a Z boson is presented. The search is based on 20.3 fb(-1) of proton-proton collision data at a center-of-mass energy of 8 TeV recorded with the ATLAS detector at the LHC. The H(±) boson is assumed to be produced via vector-boson fusion and the decays W(±)→qq' and Z→e(+)e(-)/μ(+)μ(-) are considered. The search is performed in a range of charged Higgs boson masses from 200 to 1000 GeV. No evidence for the production of an H(±) boson is observed. Upper limits of 31-1020 fb at 95% C.L. are placed on the cross section for vector-boson fusion production of an H(±) boson times its branching fraction to W(±)Z. The limits are compared with predictions from the Georgi-Machacek Higgs triplet model.